Proceedings of the 3rd International Halal Conference (INHAC 2016) (Springer Singapore, 2018)
This book contains selected papers which were presented at the 3rd International Halal Conference (INHAC 2016), organized by the Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM) Shah Alam, Malaysia. It addresses halal-related issues that are applicable to various industries and explores a variety of contemporary and emerging issues. Highlighting findings from both scientific and social research studies, it enhances the discussion on the halal industry (both in Malaysia and at the international level), and serves as an invitation to engage in more advanced research on the global halal industry.